Facilitating acquisition of critical thinking skills using jigsaw instructional method - Shrivastava, Saurabh RamBihariLal; Bobhate, Prateek Sudhakar; Mendhe, Harshal Gajanan (Indian Journal of Community Health, 2025)
For a successful professional career as a medical practitioner, it is vital that students must be trained in critical thinking during their period of undergraduate training. Critical thinking enables students and healthcare professionals to analyze clinical features, comprehend patient history, and prescribe specific laboratory or radiological tests to reach a correct diagnosis. The employment of the jigsaw method in theory or clinical training plays a crucial role in the acquisition of critical thinking skills by medical students. In conclusion, the employment of the jigsaw method for teaching-learning as one of the pedagogical approaches in medical training is crucial in the development of critical thinking skills. It is the need of the hour that medical teachers understand its scope and significance and utilize this approach to develop and refine critical thinking among medical students and thereby empower them for their future clinical practice.